Systemic inflammation induced changes in protein expression of ABC transporters and ionotropic glutamate receptor subunit 1 in the cerebral cortex of familial Alzheimer`s disease mouse model - Puris, Elena; Auriola, Seppo; Korhonen, Paula; Loppi, Sanna; Kanninen, Katja M.; Malm, Tarja; Koistinaho, Jari; Gynther, Mikko (Journal of pharmaceutical sciences, 2021)
Alzheimer's disease (AD) is an incurable disease, with complex pathophysiology and a myriad of proteins involved in its development. In this study, we applied quantitative targeted absolute proteomic analysis for investigation of changes in potential AD drug targets, biomarkers, and transporters in cerebral cortices of lipopolysaccharide (LPS)-induced neuroinflammation mouse model, familial AD mice (APdE9) with and without LPS treatment as compared to age-matched wild type (WT) mice. The ABCB1, ABCG2 and GluN1 protein expression ratios between LPS treated APdE9 and WT control mice were 0.58 (95% CI 0.44-0.72), 0.65 (95% CI 0.53-0.77) and 0.61 (95% CI 0.52-0.69), respectively. The protein expression levels of other proteins such as MGLL, COX-2, CytC, ABCC1, ABCC4, SLC2A1 and SLC7A5 did not differ between the study groups. Overall, the study revealed that systemic inflammation can alter ABCB1 and ABCG2 protein expression in brain in AD, which can affect intra-brain drug distribution and play a role in AD development. Moreover, the inflammatory insult caused by peripheral infection in AD may be important factor triggering changes in GluN1 protein expression. However, more studies need to be performed in order to confirm these findings. The quantitative information about the expression of selected proteins provides important knowledge, which may help in the optimal use of the mouse models in AD drug development and better translation of preclinical data to humans.